PENGARUH PENERAPAN SISTEM FULL DAY SCHOOL TERHADAP MOTIVASI BELAJAR PESERTA DIDIK DI SMPN 1 BEKASI - Rasyidin, Muhammad; Aldiansyah, Muhammad; Shiddiq, Noviandana Baihaqi; Putra, Purnama (LPPM Universitas Islam 45, 2024)
The full day school system is a system that can encourage increased learning motivation and character building of students at school, because learning can be done in a longer time. However, through interviews conducted with several teachers and students of SMPN 1 BEKASI, several opinions were found that were against this system. In fact, the various benefits obtained through the implementation of the full day school system still cannot eliminate some of these counter opinions. This study aims to determine the effect of the Full Day School System on learning motivation and student character building at SMPN 1 BEKASI. This study uses a quantitative method with a sample of 29 ninth grade students. So that the filled questionnaire must be 29 data according to the number of samples. This study uses simple regression analysis techniques to test the variable fullday school system on learning motivation. The results stated that there was no significant effect on the implementation of the full day school system on student learning motivation. In many cases, students actually feel exhausted or less focused when school hours are extended without any significant changes in the learning approach or a more conducive learning atmosphere.